Low-dose proton induced genetic alteration in cingulate cortex and declined its relevant cognitive function in behaviors - Kim, Gyutae; Park, Hyelim; Kim, Kyu-Sung (Frontiers in Behavioral Neuroscience, 2025)
Environmental radiation poses health risks to the central nervous system (CNS) as well as the internal organs. While the technology for managing radiation has improved, the effects of low-dose radiation in the long term are still considered as a health-related risky factor. The clinical and space radiation studies suggested cognitive threat from proton, but the inconsistent behavioral responses to low-dose proton made their cognitive effects elusive. Here, we examined the low-dose proton-induced functional changes by measuring genetic and behavioral responses. Total 54 mice (C57BL/6, 7 weeks, males) were used for this study. The genetic effects were tested using the brain tissue (cingulate cortex, CC), one of core regions for cognition, and the behavioral responses were evaluated by open field (OFT) and radial maze tests (RMT). In 4 weeks after irradiation, all genes (HSPA, GFAP, MBP, NEFL, NEFM) showed peak inflammatory responses (p < 2.05×10−3), and these reactions were resolved in 3 months, returning to the initial level of foldchanges. The behavioral changes were identified between 4 weeks and 3 months, which was after the peak genetic inflammatory period. The moving distance and the speed were maintained up to 4 weeks, but both motional factors decreased with significance after 4 weeks (p < 0.126×10−3). Unlike the results in OFT, no parameters in RMT showed a significant difference among the groups. Considering the overall results, low-dose protons induced reversible genetic alteration in the central regions over time, and their delayed effects on cognitive behaviors were limited, with consequences varying depending on the functional types of cognition. Our current findings are expected to provide critical information for the development of substantive regulations for astronauts’ health and clinical use of proton.